2011
DOI: 10.1590/s1413-86702011000500002
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of genotypes in CTX-M-producing Klebsiella pneumoniae isolated in different hospitals in Brazil

Abstract: Objective: The present study was undertaken to characterize CTX-M ESBL-producing Klebsiella pneumoniae collected from hospitals in different cities of Brazil. Material and Methods: Eighty-five K. pneumoniae strains isolated from hospitalized patients in six different hospitals of three cities of Brazil were analyzed. ESBL production was confirmed by the standard double-disk synergy test and the Etest®. The MIC 50 and MIC 90 for ESBL-producing isolates were determined by the Etest® method. The antimicrobial sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
(27 reference statements)
2
7
0
Order By: Relevance
“…Few studies have evaluated the presence of class 1 integrons in K. pneumoniae isolates from the Brazilian northeast 27 . Chagas et al 20 showed that all K. pneumoniae ESBL-producing isolates from Rio de Janeiro and São Paulo, Brazil carried class 1 integrons. Ahangarzadeh Rezaee et al 13 found that integrons were widely prevalent in clinical isolates of K. pneumoniae from northwestern Iran and were associated with multidrug resistance.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have evaluated the presence of class 1 integrons in K. pneumoniae isolates from the Brazilian northeast 27 . Chagas et al 20 showed that all K. pneumoniae ESBL-producing isolates from Rio de Janeiro and São Paulo, Brazil carried class 1 integrons. Ahangarzadeh Rezaee et al 13 found that integrons were widely prevalent in clinical isolates of K. pneumoniae from northwestern Iran and were associated with multidrug resistance.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…Classes 1, 2, and 3 are the most commonly detected 19 . Class 1 integrons are the most widespread and have been frequently found in extended-spectrum β-lactamase (ESBL)-producing clinical isolates of Enterobacteriaceae, including K. pneumoniae 6,13,16,20,21 . Class 2 integrons occur less frequently in ESBL-producing Escherichia coli and K. pneumoniae, and class 3 integrons are rarely found in ESBL-producing K. pneumoniae 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Production of extendedspectrum β-lactamase (ESBL) is the basic reason for the multidrug resistance in Gram negative bacteria throughout the world. Since 1983 when the first ESBL enzymes were described in Europe (Germany), there is an alarming increase in the incidence of ESBL-producing bacteria (4)(5)(6). ESBL-producing K. pneumoniae strains are one of the most important problems associated with nosocomial outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…This factor might also explain the increased rates of susceptibility to ceftazidime among Gram-negative rod-shaped organisms observed in our facility. However, another possible explanation is that there is a higher prevalence of cefotaximase (CTX-M)-producing Enterobacteriaceae strains in Brazil than in other countries (24) . The present study aimed at providing assessment data that might infl uence pharmacodynamic clinical guidelines for the selection of appropriate empirical antibiotic therapies for bacteremia.…”
Section: Discussionmentioning
confidence: 99%